(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Our understanding of consumer decision-making has been transformed by behavioural economics, which combines psychological insights with traditional economic theory. Research in this field challenges the rationality-based assumptions of conventional economics by examining the impact of customers’ emotions, social influences, and cognitive biases on their purchase choices. This article will examine key concepts in behavioural economics and how they may guide policymakers and businesses to better serve their constituents. Behavioural economics is a new field that combines insights from psychology and economics to provide a fresh look at consumer decision-making. Standard economic theory states that people act rationally and choose courses of action that maximise their own gain.